2012
DOI: 10.3892/ijmm.2012.884
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of alpinetin in BxPC-3 pancreatic cancer cells

Abstract: Alpinetin is a novel plant flavonoid derived from Alpinia katsumadai Hayata, found to possess strong anticancer effects. However, the antitumor effect of alpinetin on pancreatic cancer cells and the detailed mechanism remain unclear. The aim of this study was to investigate alpinetin's beneficial effect on pancreatic cancer and the possible molecular mechanism involved. Pancreatic cancer cell lines were treated with alpinetin at various doses and for different times, and the effect of alpinetin on cell growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…1A) is a natural flavonoid primarily derived from the roots or seeds of Alpinia katsumadai Hayata that is known to exhibit antibacterial, anti-inflammatory and other important therapeutic properties (12)(13)(14)(15)(16)(17)(18). In previous studies, alpinetin was reported to inhibit proliferation of human tumor cells, including lung cancer and gastroenteric cancer cells (12)(13)(14)(15)(16)19), indicating the potential anticancer properties of this compound. However, the effects of alpinetin on ovarian cancer cells and its underlying mechanisms of action remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1A) is a natural flavonoid primarily derived from the roots or seeds of Alpinia katsumadai Hayata that is known to exhibit antibacterial, anti-inflammatory and other important therapeutic properties (12)(13)(14)(15)(16)(17)(18). In previous studies, alpinetin was reported to inhibit proliferation of human tumor cells, including lung cancer and gastroenteric cancer cells (12)(13)(14)(15)(16)19), indicating the potential anticancer properties of this compound. However, the effects of alpinetin on ovarian cancer cells and its underlying mechanisms of action remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…According to another report, apoptosis of brain glioma cells is closely related to the mitochondrial pathway (16)(17)(18). The inter-shifting of Bcl-2 and Bax proteins releases cytochrome c and activates the caspase family to finally induce apoptosis (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…A Perkin-Elmer LS-50B fluorospectrophotometer was used to measure the alterations in fluorescence intensity when the excitation wavelength was 380 nm and emission wavelength was 460 nm. Previously described methods were used (19).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of caspase-3 and -9 activities was performed as described previously (13). The Perkin-Elmer LS-50B fluorescence spectrophotometer (Waltham, MA, USA) was used to measure changes in fluorescence intensity at excitation and emission wavelengths of 380 and 460 nm, respectively.…”
Section: Detection Of Apoptosis By Annexin V-fitc/pi Double Stainingmentioning
confidence: 99%